2022
DOI: 10.3390/tropicalmed7110390
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arbovirus Infection in Arthritogenic Pain Manifestation—A Systematic Review

Abstract: The number of publications on the development of arthritic pain after CHIKV infection is increasing; however, there is still a gap in the pathophysiological mechanisms that explain these outcomes. In this review, we conducted a descriptive analysis of the findings of patients to understand their prognosis and to explore therapeutic options. Here, we searched the Cochrane, BVS, PubMed, and Scielo databases using the keywords “arthritis”, “pain”, “arbovirus”, “disease”, “arthritogenic”, and “arthralgia” during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…Studies in animal models and human patients have shown that CHIKV can persist in target tissues, such as joints, even after its elimination from the bloodstream. 7 , 9 This suggests that the continuous presence of the virus in tissues may trigger a chronic inflammatory response, contributing to persistent pain and progression to chronic arthritic syndrome. 7 , 9 , 10 However, the chronification of post-arboviral pain is still not fully understood, although evidence suggests it may be related to the persistence of viral RNA fragments or proteins in macrophages and monocytes, leading to cellular activation and subsequent cytokine and antibody production, as well as the induction of autoimmunity in genetically predisposed individuals.…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in animal models and human patients have shown that CHIKV can persist in target tissues, such as joints, even after its elimination from the bloodstream. 7 , 9 This suggests that the continuous presence of the virus in tissues may trigger a chronic inflammatory response, contributing to persistent pain and progression to chronic arthritic syndrome. 7 , 9 , 10 However, the chronification of post-arboviral pain is still not fully understood, although evidence suggests it may be related to the persistence of viral RNA fragments or proteins in macrophages and monocytes, leading to cellular activation and subsequent cytokine and antibody production, as well as the induction of autoimmunity in genetically predisposed individuals.…”
Section: Pathophysiologymentioning
confidence: 99%
“… 7 , 9 This suggests that the continuous presence of the virus in tissues may trigger a chronic inflammatory response, contributing to persistent pain and progression to chronic arthritic syndrome. 7 , 9 , 10 However, the chronification of post-arboviral pain is still not fully understood, although evidence suggests it may be related to the persistence of viral RNA fragments or proteins in macrophages and monocytes, leading to cellular activation and subsequent cytokine and antibody production, as well as the induction of autoimmunity in genetically predisposed individuals. 9 , 10 Prolonged immune cell activation and induction of autoimmunity in predisposed individuals may also contribute to symptom persistence.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Another report studies the seroprevalence of DENV, ZIKV, or CHIKV in Bangphae District, Ratchaburi Province, Thailand, via enzyme-linked immunosorbent assays and rapid diagnostic tests [ 9 ]. Furthermore, one review details the role of CHIKV infection in arthritogenic pain, which appears to be comparable to rheumatoid arthritis as both diseases share common symptoms [ 10 ].…”
mentioning
confidence: 99%